The association between anti-Müllerian hormone and vitamin 25(OH)D serum levels and polycystic ovarian syndrome in adolescent females - Samantha Simpson; David B. Seifer; Veronika Shabanova; Anna Y. Lynn; Catherine Howe; Erin Rowe; Sonia Caprio; Alla Vash-Margita (BMC, 2020)
Abstract Background High anti-Müllerian hormone (AMH) levels and 25-hydroxyvitamin D [25(OH)D] deficiency have been associated with polycystic ovarian syndrome (PCOS) in adult women, and implicated in its pathogenesis. Herein we determined if the level of both AMH and 25(OH)D are altered in adolescent females with clinical features of PCOS. Methods This is a cross-sectional study utilizing a retrospective chart review of 128 patients aged 12-20 referred to an academic adolescent gynecology and endocrinology clinic for an evaluation of suspected PCOS. Unadjusted comparisons of AMH and 25(OH)D distributions between subjects with and without PCOS were performed using the Wilcoxon Rank Sum test. Quantile regression was used to compare the median AMH and 25(OH)D between subject groups; adjusting for race, ethnicity, BMI, insurance type, age, and season when bloodwork was performed. Results Seventy-four subjects were classified as having PCOS by meeting ≥2 of the three Rotterdam diagnostic criteria, and 47 subjects met only one Rotterdam diagnostic criteria, and were used as the comparative non-PCOS group. There were statistically significant unadjusted differences in median levels of AMH and 25(OH)D. In the adjusted analyses, median AMH was significantly higher in the PCOS group compared to the non-PCOS group (+ 2.39 ng/mL, 95% CI 0.43, 4.35, p = 0.018); 25(OH)D was significantly lower in the PCOS group (− 9.01 ng/mL, 95% CI -14.49, − 3.53 p = 0.001). In our sample, adolescents in both groups had insufficient 25(OH)D level (22 ng/mL) and elevated BMI (32.2 kg/m2). Conclusions Adolescents with PCOS display high levels of AMH and low 25(OH)D levels. Since traditional clinical markers of PCOS may be physiologic in adolescents, AMH and 25(OH)D may be used as surrogate markers of PCOS risk in adolescents.